Genetic and biochemical definition of the Hedgehog receptor - Zheng, Xiaoyan (Cold Spring Harbor Laboratory Press, 2010)
Although the transporter-like protein Patched (Ptc) is genetically implicated in reception of the extracellular Hedgehog (Hh) protein signal, a clear definition of the Hh receptor is complicated by the existence of additional Hh-binding proteins and, in Drosophila, by the lack of physical evidence for direct binding of Hh to Ptc. Here we show that activity of Ihog (Interference hedgehog), or of its close relative Boi (Brother of Ihog), is absolutely required for Hh biological response and for sequestration of the Hh protein to limit long-range signaling. We demonstrate that Ihog interacts directly with Ptc, is required for presentation of Ptc on the cell surface, and that Ihog and Ptc are both required for high-affinity Hh binding. On the basis of their joint roles in ligand binding, signal transduction, and receptor trafficking, we conclude that Ihog and Ptc together constitute the Drosophila Hh receptor.